CONCEPTUAL ASPECT OF DUCHENNE MUSCULAR DYSTROPHY - Bharvi B, Trivedi; Raksha, Mer; Jasmin, Viramgami (International Journal of Ayurveda and Pharma Research, 2017)
The muscular dystrophies (MD) are a group of genetic diseases characterized by progressive weakness and degeneration of the skeletal muscles that control movement. DMD is one among the most common muscular disorders. The incidence is 1:3500 live male birth. It is X-linked recessive disease caused by a deficiency of a normal muscle protein called dystrophin, which maintains the integrity of the muscle cell wall. Degeneration of the skeletal muscles, which control movement leading to lose the ability to stand, walk and loss of ambulation before 10 years, with progression of the disease most patients succumb to death in their early 20s. Disease is having bad prognosis if the treatment start in early stages of the disease, it may slow or stop the progressive degeneration of muscles. As there is no specific treatment in any system of medicine for DMD, in modern therapeutic approach of muscular dystrophy is represents on corticosteroids, physical therapy, respiration assistance and gene therapy. All major neuromuscular disorders are identified with Vata Dosha. In Ayurveda this pathogenesis can be clearly understood by the concept of Adi bala pravritta vyadhi. Here the pathogenesis occurs due to the Beejabhagavayava Dushti which leads to Mamsa Vata Dushti. The Ayurvedic treatments relevant to Rasayana group of herbo-mineral medicines and specified Panchakarma therapies have definite protective influence and long survival on Dhatu Kshaya. Keep upon this view in present study the therapies and medicines is useful for DMD is taken with their logical understanding.